2018
DOI: 10.3389/fmicb.2018.00543
|View full text |Cite
|
Sign up to set email alerts
|

High Variability in Cellular Stoichiometry of Carbon, Nitrogen, and Phosphorus Within Classes of Marine Eukaryotic Phytoplankton Under Sufficient Nutrient Conditions

Abstract: Current hypotheses suggest that cellular elemental stoichiometry of marine eukaryotic phytoplankton such as the ratios of cellular carbon:nitrogen:phosphorus (C:N:P) vary between phylogenetic groups. To investigate how phylogenetic structure, cell volume, growth rate, and temperature interact to affect the cellular elemental stoichiometry of marine eukaryotic phytoplankton, we examined the C:N:P composition in 30 isolates across 7 classes of marine phytoplankton that were grown with a sufficient supply of nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
76
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 41 publications
(58 reference statements)
20
76
2
Order By: Relevance
“…S5). This is presumably caused by the vast range in cell size across species, that affects growth rate, nitrogen acquisition and elemental composition Edwards et al 2015a, b;Garcia et al 2018). The intraspecific variation in K 1/2 values for nitrogen, however, was comparable to the earlier reported interspecific variation across marine phytoplankton species (Fig.…”
Section: Lettersupporting
confidence: 59%
See 1 more Smart Citation
“…S5). This is presumably caused by the vast range in cell size across species, that affects growth rate, nitrogen acquisition and elemental composition Edwards et al 2015a, b;Garcia et al 2018). The intraspecific variation in K 1/2 values for nitrogen, however, was comparable to the earlier reported interspecific variation across marine phytoplankton species (Fig.…”
Section: Lettersupporting
confidence: 59%
“…; Edwards et al . , b; Garcia et al ). The intraspecific variation in K 1/2 values for nitrogen, however, was comparable to the earlier reported interspecific variation across marine phytoplankton species (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The C:N ratios observed here for C. gelidus at 0 • C (7.48 ± 0.83 mol C mol −1 N) are at the upper bound of values reported for other polar diatoms by Lacour et al (2017) in the -0.5 to 5 • C Levasseur et al, 1993 temperature range (average = 5.77 ± 0.52 mol C mol −1 N), by Garcia et al (2018) at 2 • C (average = 6.09 ± 0.59 mol C mol −1 N, range 5.72-6.97), and at 2 • C [average = 5.99 ± 0.99 mol C mol −1 N, range 5.01-7.51; calculated using the dataset of , for cells in exponential growth phase]. However, the C:N ratio of C. gelidus is remarkably close to the average reported by Sarthou et al (2005) for temperate diatoms (7.3 ± 1.2 mol C mol −1 N, range 5.0 to 9.7 mol C mol −1 N) and suggests that this species is able to incorporate more C per unit N in its biomass than most other Arctic diatoms.…”
Section: Similarities and Contrasts Between The Elemental Ratios Of Csupporting
confidence: 56%
“…These resting stages can survive for at least a century in the sediment, and upon revival, we can study adaptations to eutrophication within local Skeletonema populations (McQuoid et al, 2002;Härnström et al, 2011;Ellegaard et al, 2018). A recent study demonstrated higher variability of diatoms in carbon, nitrogen and phosphorus quota on a clone specific level compared to other phytoplankton (Garcia et al, 2018). We hypothesized that a diversity of nutrient demands occurs even at a single-cell level in diatoms including Skeletonema.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship led to the theory of a fixed stoichiometric ratio between carbon, nitrogen and phosphorus (106:16:1) in phytoplankton based on the ratio at which the nutrients are consumed by phytoplankton during growth (Redfield, 1934;1958). Throughout the last decades, this concept has been reconsidered based on culture studies indicating large variations in organic matter nutrient ratios, associated to nutrient availability, light and temperature (Geider and LaRoche, 2002;Gruber and Deutch, 2014;Garcia et al, 2018). Since the introduction of fertilizers within the agroindustry during the last century, concentrations of nitrate, particularly in coastal areas, have increased.…”
Section: Introductionmentioning
confidence: 99%